Interaction of Plasmin with Tranexamic Acid and α2 Plasmin Inhibitor in the Plasma and Clot - Takada, Akikazu; Ito, Takeshi; Takada, Yumiko (Thrombosis and Haemostasis, 1980)
Interaction of urokinase (UK) activated plasmin with tranexamic acid and α2 plasmin inhibitor (α2PI) was studied by using a chromogenic substrate (S-2251) and immunoelectrophoresis. Plasma was activated by UK (P+U) in the presence of tranexamic acid (P+U + t) or in the presence of thrombin (P+U+thr) and thrombin plus tranexamic acid (P+U+thr+t). These mixtures were incubated for 10, 20, and 30 min at 37°C, then an aliquot of each mixture was added to S-2251, and incubated for 3 or 10 min at 37°C. Hydrolysis of S-2251 after 3 min incubation was significant in the presence of tranexamic acid or clot formation, thus the presence of tranexamic acid or clot formation enhancing the UK activation of plasminogen in both plasma and clot. Hydrolysis of S-2251 after 10 min incubation was higher in the presence of tranexamic acid than in its absence or clot formation without tranexamic acid. Tranexamic acid seems to be more effective in enhancement of activation of plasminogen by UK than clot formation. Plasmin formed by UK was coexistent with α2PI in the plasma in contrast to a purified system in which α2PI formed a complex with plasmin instantaneously. In an even purified system, clot formation and the presence of tranexamic acid protected plasmin from its inactivation by α2PI to some extent.
Keywords: Plasmin; α2 plasmin inhibition; Tranexamic acid; Urokinase; Crossed immunoelectrophoresis